2009
DOI: 10.1007/s10681-009-9908-5
|View full text |Cite
|
Sign up to set email alerts
|

Do different production environments justify separate maize breeding programs?

Abstract: DiVerent production environments are being adopted by farmers. Therefore, allocation of resources to breeding research that targets diVerent production environments should be continuously assessed. Agronomists should conduct extensive hybrid £ production environment interaction research before recommending breeders to conduct separate breeding programs for each production environment. The lack of interactions between genotypes and production environments (e.g., tillage) would not justify conducting separate br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…Our results show that stored water at harvest was higher under non-tillage (Table 1) even when the stored water at seeding was the same ( Carena et al (2009) showed that there is no need to develop cultivars specific to non-tillage because the cultivars that were developed under conventional tillage systems performed relatively the same under non-tillage. In line with the above opinion, some authors consider that since the germplasm within breeding programs is continually changing and farming practices change with time, there is no need to drive parallel breeding programs (Sip et al 2009).…”
mentioning
confidence: 61%
“…Our results show that stored water at harvest was higher under non-tillage (Table 1) even when the stored water at seeding was the same ( Carena et al (2009) showed that there is no need to develop cultivars specific to non-tillage because the cultivars that were developed under conventional tillage systems performed relatively the same under non-tillage. In line with the above opinion, some authors consider that since the germplasm within breeding programs is continually changing and farming practices change with time, there is no need to drive parallel breeding programs (Sip et al 2009).…”
mentioning
confidence: 61%
“…We have identified cost/effective, and less input oriented breeding strategies to optimize water under extreme conditions. We intend to identify the ones for N use efficiency under similar conditions based on the principles addressed by Carena et al (2009a). Certain genotypes have demonstrated to be more stable across environments which should be more tolerant to climate change (Carena et al 1998).…”
Section: The Future: Developing Breeding Methods and Cultivars For Admentioning
confidence: 99%
“…It is, therefore, necessary to evaluate genotype x N and genotype x soil type interactions to determine the need/ lack of need for duplicating cultivar development programs under different environmental conditions. We have previously determined that no interactions are present when testing different plant densities and tillage systems in maize , Hyrkas and Carena 2005, Carena et al 2009a. We have the opportunity to challenge current and past production research by addressing the real facts behind sustainability.…”
Section: The Future: Developing Breeding Methods and Cultivars For Admentioning
confidence: 99%
“…Further, PREs El Quebrachal in-season sowing (EQ), Fernandez in-season and late sowings (FE), VD, and Puerta Grande in-season and late sowings (PG) were identified within the subtropical GR (Fig. Carena et al (2009) reported evidence of several genotype ´ tillage or soil type interaction studies conducted on maize in the period 1983 to 2006. Therefore, those locations or planting windows that fell within the same PRE (e.g., Carmen late and Rojas late and very late sowings in CR2) might be treated as replications, giving redundant information (Setimela et al, 2005).…”
Section: Climatic Production Environmentsmentioning
confidence: 92%